ANALISIS PENYERAPAN TENAGA KERJA PADA SEKTOR USAHA MIKRO KECIL DAN MENENGAH DI KABUPATEN SUMBAWA - Suci Lestari; Marisa Sutanty (Jurnal Ekonomi & Bisnis, 2023)
This study aims to analyze labor absorption in the MSME sector in Sumbawa District. The factors thought to influence labor absorption in the MSME sector in Sumbawa District are sales rates and wage rates. The type of this study was associative. The type of data used was quantitative data in the form of sales data, wages and number of labors obtained from documen or archip recording financial reports for MSMEs in Sumbawa District which is the subject of the study. The population that is the subject of this study is all 153 milk candy MSMEs in Penyaring Village, Sumbawa District. Determining the sample in this study used a census sampling technique, which is a sampling technique when all members of the population are used as samples. Thus, the sample in this study was 153 MSMEs in Sumbawa District. All of data was studied using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determinant coefficient testing (R2). The results of this study showed that the sales rates and wage rates have a positive and significant effect on labor absorption in the MSME sector in Sumbawa District, either partially or simultaneously. The ability of the sales rates and wage rates variables to influence the labor absorption in the MSME sector in Sumbawa District is 74.1%, while the remaining 25.1% is influenced by other variables not examined, such as capital, productivity level and education level of the labors.